2011
DOI: 10.1007/s00267-011-9736-y
|View full text |Cite|
|
Sign up to set email alerts
|

Restoring Ecological Integrity in Highly Regulated Rivers: The Role of Baseline Data and Analytical References

Abstract: The goal of restoring ecological integrity in rivers is frequently accompanied by an assumption that a comparative reference reach can be identified to represent minimally impaired conditions. However, in many regulated rivers, no credible historical, morphological or process-based reference reach exists. Resilient restoration designs should instead be framed around naturalization, using multiple analytical references derived from empirically-calibrated field- and model-based techniques to develop an integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 69 publications
0
41
0
1
Order By: Relevance
“…The increased understanding achieved over the last decade in riparian vegetation pattern and functioning provides a solid basis for rational resource management in med-river ecosystems (e.g., Downs et al, 2011). Approaches with strong precedent include releasing environmental flows to benefit riverine and riparian species (Hughes & Rood, 2003;Rood et al, 2005), as well as non-native species management .…”
Section: Applications To Management Of Med-region Riparian Ecosystemsmentioning
confidence: 99%
“…The increased understanding achieved over the last decade in riparian vegetation pattern and functioning provides a solid basis for rational resource management in med-river ecosystems (e.g., Downs et al, 2011). Approaches with strong precedent include releasing environmental flows to benefit riverine and riparian species (Hughes & Rood, 2003;Rood et al, 2005), as well as non-native species management .…”
Section: Applications To Management Of Med-region Riparian Ecosystemsmentioning
confidence: 99%
“…The necessity of a control, however, depends on the type of question being addressed. Impact studies (those without a control) can provide important insights into rates of physical and ecological changes after dam removal . However, these studies do not permit the interpretation of post‐removal changes in the context of pre‐removal or control site conditions (e.g., upstream conditions).…”
Section: Characteristics Of Dam‐removal Studiesmentioning
confidence: 99%
“…Impact studies (those without a control) can provide important insights into rates of physical and ecological changes after dam removal. 39 However, these studies do not permit the interpretation of post-removal changes in the context of pre-removal or control site conditions (e.g., upstream conditions). Whether a study employs a temporal and/or spatial control depends on funding availability, sufficient advance notice of dam removal, the existence of an appropriate control site (e.g., McHenry and Pess 40 ), and the types of research questions being addressed.…”
Section: Characteristics Of Dam-removal Studiesmentioning
confidence: 99%
“…This is crucial for the rivers studied because their low energy implies long-term morphological adjustments for which the controlling factors are difficult to identify in contrast with high energy streams which can rapidly adjust their morphology to changes in governing conditions, making them easier to track (e.g., Liébault and Piégay, 2002;Comiti, 2012). We aim to demonstrate the relevance of a holistic approach to these specific fluvial systems that includes the collection of baseline data (Downs et al, 2011) and understanding of the trajectories over the long-term to develop objectives for sustainable management (Brown, 1997(Brown, , 2002Downs and Gregory, 2004;Brierley and Fryirs, 2005;Froyd and Willis, 2008;Hughes et al, 2008;Higgs et al, 2014;Kondolf and Podolak, 2014). The extent to which present understanding of the low energy systems is, and could be, used is discussed and the requirements for future research identified.…”
Section: Introductionmentioning
confidence: 99%